2016
DOI: 10.1139/cjas-2015-0193
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the variation in the daily excretion of faecal constituents and digestibility predictions in beef cattle fed feedlot diets using near-infrared spectroscopy

Abstract: Six heifers were individually housed and assigned to once (FF1) or twice (FF2) daily feeding regimes over backgrounding and finishing periods. Following adaptation, total faecal collections were conducted at 4-h intervals and at 24-h intervals over 4 d, and near-infrared spectroscopy (NIRS) was used to predict faecal organic matter (OM), starch, nitrogen (N), neutral detergent fibre (NDF), acid detergent fibre (ADF), and acid detergent lignin (ADL). At each interval, NIRS calibrations were used to estimate fae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
1
9
1
Order By: Relevance
“…The ADL content in this study was similar to that found by Jancewicz et al (2016), in a study performed on beef heifers fed a forage-based diet consisting of 50:50 grass hay:barley silage diet (on a DM basis). The faecal N content was comparable to that reported by Jancewicz et al (2016) and , although the CP content of the diet was lower in the present trial (12.81 versus 13.5 and 13.4-14.6%DM). This could be due to a lower digestibility of the dietary protein fed in our trial.…”
Section: Chemical and Nirs Evaluation Of Faecessupporting
confidence: 89%
See 2 more Smart Citations
“…The ADL content in this study was similar to that found by Jancewicz et al (2016), in a study performed on beef heifers fed a forage-based diet consisting of 50:50 grass hay:barley silage diet (on a DM basis). The faecal N content was comparable to that reported by Jancewicz et al (2016) and , although the CP content of the diet was lower in the present trial (12.81 versus 13.5 and 13.4-14.6%DM). This could be due to a lower digestibility of the dietary protein fed in our trial.…”
Section: Chemical and Nirs Evaluation Of Faecessupporting
confidence: 89%
“…The aNDF and ADF content of faeces was slightly higher in comparison to those reported by other authors on beef heifers (Jancewicz et al 2016) and beef steers which is explained by the greater amount of fibre sources in our diets. The ADL content in this study was similar to that found by Jancewicz et al (2016), in a study performed on beef heifers fed a forage-based diet consisting of 50:50 grass hay:barley silage diet (on a DM basis). The faecal N content was comparable to that reported by Jancewicz et al (2016) and , although the CP content of the diet was lower in the present trial (12.81 versus 13.5 and 13.4-14.6%DM).…”
Section: Chemical and Nirs Evaluation Of Faecescontrasting
confidence: 79%
See 1 more Smart Citation
“…Although none of the average fecal concentrations reported in the commercial feedlot samples appeared unusual, the largest discrepancy identified occurred with fecal NDF, which was on average 3% lower than previous estimates from research feedlot studies. This is not likely due to an error with NIRS as the average fecal NDF in a subset of these samples that were analyzed using wet chemistry was also lower than reported in previous studies (46.0% ± 8.02%; Jancewicz et al 2016). As we did not analyze the diets that were fed to the commercial feedlot cattle, it was impossible to determine if the lower fecal NDF was a result of lower NDF intake.…”
Section: Characterization Of Fecal Samplesmentioning
confidence: 74%
“…Research by Owens and Zinn has shown that the accuracy of starch digestibility predictions can be improved by including additional variables such as fecal N (Zinn et al 2011), dry matter (DM) or organic matter (OM) digestibility, and starch intake (Owens et al 2016). Methods to predict other nutrient digestibilities, particularly neutral detergent fiber (NDF), from their fecal concentrations have been examined (Fredin et al 2014;Jancewicz et al 2016;Owens et al 2016), as well as indirect relationships between OM digestibility and fecal crude protein (CP) (Lukas et al 2005). Because fecal samples contain information relevant to feed digestion, monitoring how efficiently cattle are utilizing nutrients could directly benefit the efficiency and profitability of feedlot cattle production.…”
Section: Introductionmentioning
confidence: 99%